A two-stage model for rate-dependent inverse hysteresis in reluctance actuators. (1st January 2020) - Xu, Yunlang; Li, Xiaoping; Yang, Xiaofeng; Yang, Zhile; Wu, Liwei; Chen, Qingsheng
Highlights: A two-stage model used for rate-dependent inverse hysteresis is proposed. The new model is suitable for both symmetric and asymmetric hysteresis. A dynamic inverse operator is designed for Stage-two model. The two-stage model is applied as a feedforward compensator. Abstract: Reluctance actuators, being capable of providing high force densities, have been widely adopted for solving the task of high force applications. However, the strong non-linearity in the inherent hysteresis considerably limits the application performance of reluctance actuator in the output of high-precision force, in particular when hysteresis is coupled with eddy effects which gives rise to a rate-dependent hysteresis effect in the actuator. Feed-forward compensation technologies, which utilize the inverse hysteresis model as the compensator, have been proved to be effective in alleviating hysteresis non-linearities over different excitation frequencies. In the study, a new two-stage model for rate-dependent inverse hysteresis is proposed, which can directly model the inversion of rate-dependent hysteresis regardless of the hysteresis loop is symmetric or not. The proposed model is applied as a feed-forward compensator to linearise the rate-dependent hysteresis effects in the reluctance actuator at a range of excitation frequencies between 1 and 60 Hz. Comprehensive numerical simulations and real-world experiments are implemented on the reluctance actuator to validate the effectiveness of the new model. The results show that the proposed Two-stage hysteresis model can accurately and robustly demonstrate the inversions of rate-dependent hysteresis, and the hysteresis non-linearities in the reluctance actuator are effectively suppressed by the two-stage model-based compensator with less insensitivity to various noise.